Modern drama : a very short introduction (Oxford University Press, 2016)
"The story of modern drama is a tale of extremes, testing both audiences and actors to their limits through hostility and unpredictability. It is a truly international phenomenon, encompassing works by playwrights such as Ibsen, Chekhov, Shaw, Miller, Beckett, and Churchill, which are vibrant and diverse in both text and performance. This Very Short Introduction explores the major developments of modern drama from 1880 to the present. Ranging from early modernist theatre through post-war developments to more recent and contemporary theatre, Shepherd-Barr tracks the emergence of new theories from the likes of Stanislavsky, Brecht, and Grotowski alongside groundbreaking productions to illuminate the fascinating evolution of modern drama"--